Answer:
Step-by-step explanation:
it is a downward parabola cutting x-axis at (-3,0),(1,0)
f(x)=-(x+3)(x-1)
=-(x²+2x-3)
=-(x²+2x+1-1-3)
=-(x+1)²+4
vertex is (-1,4)
3x = 45
(–2x3y2 + 4x2y3 – 3xy4) – (6x4y – 5x2y3 – y5)
Answer:
Step-by-step explanation:
We have to find the difference of the polynomials
Let us distribute the negative over the parenthesis
Now, group the like terms
Combine the like terms
Rearrange the polynomial, we get
Answer:
Step-by-step explanation:
well just go to brainly my my 67
Answer:
r = 1
Step-by-step explanation:
We can combine like terms, getting -3r = -3.
Then we can divide both sides by -3, and get r = 1.
Answer:
r = 1
Step-by-step explanation:
First, we'll simplify
-5r + 2r = -3
-3r = -3
Then, we divide
-3 divided by - 3 is equal to 1
Therefore, r = 1
Hope this helps!